The construction of identity starting from the cultures of femininity, masculinity, family and birth: Some considerations and 34 clinical vignettes - Paniccia, Rosa Maria; Atzori, Elisabetta; Assante Del Leccese, Rossella; Avilloni, Kristian; Baldi, Roberta; Battisti, Nadia; Calisse, Maria Vittoria; Capozzi, Veronica; Cuccurese, Maria Teresa; D'Antona, Elisa; Diciolla, Rossana; Di Ninni, Anna; et al. (Quaderni di Psicologia Clinica, 2024)
This article is the result of the sharing of study and reflection on the construction of identity between professionals involved in clinical psychological intervention. We explored some contemporary cultures, seen as references for the organization of identity, concerning femininity, masculinity, the couple, the family, birth, working on a comparison between emotions prescribed by the context in relation to these events and emotions experienced, as can be traced both in the social mandate and in clinical psychological intervention. Finding ourselves, in this last case, often faced with disorientation and conflicts of clients in feeling the distance between prescribed and experienced emotions, and our prejudices to be elaborated so as not to become, without awareness, uncritical guardians of the emotional symbolizations foreseen by the mandate. The article concludes with the proposal of 34 short cases.